Neural correlates of a computerized attention modification program in anxious subjects - Taylor, Charles T. (Oxford University Press, 2014)
Computerized attention modification is a relatively new and empirically validated treatment approach for different types of anxiety disorders. However, its neural basis and processes involved are poorly understood. This study examined the effect of a one-time application of an attention modification program (AMP) on neural substrates underlying emotion processing in individuals with high social anxiety. Fourteen individuals with elevated social anxiety symptoms completed an emotional face processing task during functional magnetic resonance imaging before and after AMP, and were subsequently exposed to a laboratory stressor. Results revealed the following: First, there was attenuated activation from pre- to post-AMP in the bilateral amygdala, bilateral insula and subgenual anterior cingulate cortex. Second, post-AMP, individuals exhibited increased activation in several regions of the prefrontal cortex (PFC). Third, those individuals with greater enhancement of ventromedial PFC activation after AMP showed diminished attentional allocation for threat and attenuated anxiety reactivity to the stressor. We conclude that AMP exerts effects that are similar to those previously reported for standard anxiolytics; however, it also appears to foster deployment of top–down brain processes aimed to regulate anxiety.